2019
DOI: 10.1016/j.tranon.2019.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing May Discriminate Extreme Long-term versus Short-term Survival in Patients with Metastatic Small Cell Lung Cancer (SCLC)

Abstract: BACKGROUND: Molecular underpinnings that may prognosticate survival could increase understanding of small cell lung cancer (SCLC) tumor behavior. Here, we report the clinicopathological characteristics and biomarker profiles of short-term (ST) versus long-term (LT) survival in patients with metastatic SCLC. METHODS: Of the 876 consecutive metastatic SCLC patients receiving standard of care therapy, 44 met the definition of LT and 91 for ST, respectively. Available FFPE tumor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…ERBB4 mutations are also common in SCLC and may be associated with extreme long‐term and short‐term survival rates in metastatic SCLC patients. 12 DNA damage repair (DDR) pathway analysis showed that BRCA1 mutation is one of the DDR mutations commonly detected in SCLC patients in China, which may indicate sensitivity to corresponding target therapy. 9 There are few studies related to LRP1B, and in MPLCs, the mutations may be associated with higher TMB value and programmed death‐ligand 1 expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ERBB4 mutations are also common in SCLC and may be associated with extreme long‐term and short‐term survival rates in metastatic SCLC patients. 12 DNA damage repair (DDR) pathway analysis showed that BRCA1 mutation is one of the DDR mutations commonly detected in SCLC patients in China, which may indicate sensitivity to corresponding target therapy. 9 There are few studies related to LRP1B, and in MPLCs, the mutations may be associated with higher TMB value and programmed death‐ligand 1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Co‐mutations of TP53 and RB1 were found in both lung lesions, which provided a basis for the diagnosis of SCLC. ERBB4 mutations are also common in SCLC and may be associated with extreme long‐term and short‐term survival rates in metastatic SCLC patients 12 . DNA damage repair (DDR) pathway analysis showed that BRCA1 mutation is one of the DDR mutations commonly detected in SCLC patients in China, which may indicate sensitivity to corresponding target therapy 9 .…”
Section: Discussionmentioning
confidence: 99%